The Effects of EU-Funded Enterprise Grants on Firms and Workers - Balázs Muraközy; Álmos Telegdy (Institute of Labor Economics (IZA), 2020)
This paper investigates the effects of non-repayable enterprise grants financed from the European Union's Structural and Cohesion Funds on firm outcomes in Hungary using firm- and worker-level information on all rejected and successful grant applications between 2004-2014. In our model, after paying the fixed cost of applying, firms can purchase capital at a reduced marginal cost and they share the rent generated from the grant with their workers. In line with the model's predictions, larger than average, more productive and faster growing firms are more likely to apply for a grant. We combine panel regression methods with matching techniques to estimate the effect of grants by comparing successful and unsuccessful applicants' outcomes. Subsidized firms increase their employment, sales, capital-to-labor ratio and labor productivity, but not total factor productivity. The skill composition of workers is not affected by the grant but wages grow, especially for skilled workers. Firms winning multiple grans benefit more already from the first grant and successive grants have even larger effects. According to our simple calculations, each year's subsidy program created jobs in grant winning firms equivalent to 0.3-0.5 percent of total SME employment and contributed by 0.3-0.7 percentage points to aggregate SME productivity growth – with an annual cost often in excess of 1 percent of total SME value added. These results suggest that these grants promote firm growth, but do not lead firms to introduce new forms of production or upgrade technology.
Keywords: H25; D22; O16; J21; 330; enterprise grants; EU grants; worker effects; matched employer-employee data; Hungary